Lack of Regulatory Changes of μ-Opioid Receptors by 14-Methoxymetopon Treatment in Rat Brain. Further Evidence for Functional Selectivity - Cinar, Resat; Kekesi, Orsolya; Birkas, Erika; Fabian, Gabriella; Schmidhammer, Helmut; Szucs, Maria (Current Pharmaceutical Design, 2013)
Here we have studied regulatory changes of μ-opioid receptors accompanying in vivo 14-methoxymetopon treatments of rats. Previously, this ligand has been shown to be an extremely potent, centrally acting μ-opioid specific analgesic with low physical dependence, tolerance, respiratory depression, constipation and other side effects. Our work shows that it is a highly potent full agonist of μ-opioid receptor coupled G-protein signaling in vitro, alike the well-known opioid agonist, etorphine. However, unlike etorphine, which desensitized and down-regulated the endogenous μ-opioid receptors, 14-methoxymetopon, given to rats intraperitoneally (i.p.) either acutely or chronically, did not change the binding or G-protein signaling of μ-opioid receptors in rat brain subcellular membranes. Thereby, these data provide further evidence that there is no direct relationship between the efficacy of the ligand in signaling and its ability to internalize or desensitize the receptor. Viewed collectively with published work, it is discussed that μ-opioid receptors display functional selectivity, also called ‘biased agonism’. This concept implies that each ligand may induce unique, ligand-specific receptor conformation that can result in distinct agonist- directed trafficking and/or signal transduction pathways associated with the receptor. Ligand-specific signaling may open up new directions for designing potent analgesics that do not interact with unwanted signaling pathways, which mediate undesired side-effects, such as tolerance and dependence.
Keywords: tolerance